The Associated Press stylebook, 2022-2024 - Froke, Paula; Bratton, Anna Jo; Gross, Andale; McMillan, Jeff; Sarkar, Pia; Schwartz, Jerry; Associated Press (New York: Basic books, 2022)
"The style of The Associated Press is the gold standard for news writing. With the AP Stylebook in hand, you can learn how to write and edit with the clarity and professionalism for which their writers and editors are famous. The AP Stylebook will help you master the AP's rules on grammar, spelling, punctuation, capitalization, abbreviation, word and numeral usage, and when to use 'more than' instead of 'over.' To make navigating these specialty chapters even easier, the Stylebook includes a comprehensive index. Fully revised and updated to keep pace with world events, common usage, and AP procedures, the AP Stylebook is the one reference that all writers, editors and students cannot afford to be without. This edition contains more than 300 new and revised entries, including: A new chapter on inclusive storytelling: its importance and how to achieve it; Detailed guidance on writing about people with disabilities and disabled people; Many updates on immigration, the coronavirus, gender and race-related coverage, including the capitalization of Black and expanded use of singular they; A revised chapter on religion, with guidance on when Catholic rather than Roman Catholic should be used on first reference; A thoroughly updated chapter on using social media for reporting."--Back cover.
Foreword / Daisy Veerasingham -- What's new -- Contributors -- Stylebook: how we do it -- About the AP -- Stylebook A-Z -- Inclusive storytelling -- Artificial Intelligence -- Health and science -- Criminal justice -- Polls and surveys -- Business -- Technology -- Digital journalism -- Social media reporting -- Data journalism -- Religion -- Sports -- Punctuation -- Checklist for self-editing -- The AP statement of news values and principles -- Bibliography -- Index.
"The industry's bestselling reference for more than 30 years, essential for journalists, students, editors and writers in all professions"--Cover.
Includes bibliographical references and index.
Keywords: Journalism -- Style manuals; Journalism -- Handbooks, manuals, etc; Press law -- Handbooks, manuals, etc; Mass media -- Law and legislation; English language -- Style -- Handbooks, manuals, etc; English language -- Punctuation -- Handbooks, manuals, etc; style manuals; handbooks; Style manuals; Handbooks and manuals; Codes typographiques; Guides et manuels